1996
DOI: 10.1271/bbb.60.866
|View full text |Cite
|
Sign up to set email alerts
|

Purification, Characterization, and Crystallization of Single Molecular Species ofβ-Conglycinin from Soybean Seeds

Abstract: Four major molecular species of beta-conglycinin, alpha 3, alpha 2 beta, alpha beta 2, and beta 3, were isolated and purified from seeds of an alpha' subunit-deficient strain of soybeans (Glycine max). All components were found to be homogeneous by high pressure liquid chromatography, SDS-polyacrylamide gel electrophoresis, and amino acid and amino terminal sequence analyses. The amino acid compositions of the alpha 3 and beta 3 components agreed fairly well with the compositions deduced from the cDNA sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Another subunit, named ∃', is present only in some soya bean varieties (Coates et al 1985;Morita et al 1996). The primary structure of the ∃' subunit is still unknown, but the data suggested that this subunit is rich in sulphur-containing amino acids (Coates et al 1985).…”
Section: ∃-Conglycinin (7s Fraction)mentioning
confidence: 99%
See 1 more Smart Citation
“…Another subunit, named ∃', is present only in some soya bean varieties (Coates et al 1985;Morita et al 1996). The primary structure of the ∃' subunit is still unknown, but the data suggested that this subunit is rich in sulphur-containing amino acids (Coates et al 1985).…”
Section: ∃-Conglycinin (7s Fraction)mentioning
confidence: 99%
“…It contains three subunits (Sykes & Gayler 1981, Yamauchi et al 1981. Most recently, Morita et al (1996) succeeded in isolation and purification of four major molecular components of ∃-conglycinin, 3∀, 2∀1∃, 1∀2∃ and 3∃, from seeds of an ∀' subunit-deficient strain. By using such cultivars with a simple subunit composition and chromatography at intermediate ionic strengths over a period sufficient to reach an effective dissociation equilibrium between the monomer and dimer, they also succeeded in crystallization of single ∃-conglycinin components.…”
Section: ∃-Conglycinin (7s Fraction)mentioning
confidence: 99%
“…Soybean proteins have been analysed by different methods, with HPLC in the reversed-phase, size-exclusion, and ion-exchange modes being the most widely employed [10,11]. In some cases, the analysis of soybean proteins by HPLC has been performed for varietal identification of soybean cultivars [12 -18].…”
Section: Introductionmentioning
confidence: 99%
“…β -Conglycinin is a trimer composed of three major subunits, α , α ′ , and β , with MWs of 76, 72, and 53 kDa, respectively [65] . Another subunit, named β ′ , is present only in some soybean varieties [66,67] . All of the β -conglycinin subunits are glycoproteins and contain 4 -5% carbohydrate [68] .…”
Section: Glycinin and β -Conglycininmentioning
confidence: 99%